Status of off-bottom mariculture in wave-exposed environments. Part 1. Global inventory of extractive species commercial farms in temperate waters - Gagnon, Marc (Frontiers in Aquaculture, 2024)
There is currently a strong drive to expand aquaculture further offshore co-occurring with a rapid change of the conditions under which this activity will be practiced due to climate change. At the dawn of these profound changes a global review of the current status of technologies used commercially to grow extractive species in wave exposed environments can serve as a benchmark for future developments. Part 1 of this paper presents a systematic inventory of commercial farms in temperate exposed waters. The study area includes 5 regions in the northern hemisphere and 3 regions in the southern hemisphere and covers entirely or part of 48 countries and territories. The inventory is based on 80+ high resolution aquaculture lease maps, most of them available as Internet Web-GIS applications, that cover the entire study area with the exception of a few countries. Exposed sites are first identified from these maps using simple wave fetch criteria and this preselection is then validated using climatological data on wave height and power density (energy flux). The number of sites and the leased area are tallied by region, country, species group and production method. The longline is the production method used in more than 99% of the sites inventoried. Longline design and farm layout in 29 of these sites are reviewed. With a few exceptions, semi-submerged or fully submerged designs are used (in some cases they have been for more than 30 years) while the information on farm layout is patchy. A review of structural damage and loss of cultured biomass due to hydrodynamic forces in commercial and experimental farms confirms that surface and semi-submerged longlines are more vulnerable to large storms than fully-submerged designs.1. Enabling Open Ocean Aquaculture. 2. Anchoring Our Open Ocean Future (Ngā Punga o te Moana).